Investigation of expression quantitative trait loci and regulatory genetic variants in primary human immune cells - Makino, S (2013)
The post human genome sequence era has begun to explore various aspects of the functional genome in relation to disease including gene expression, genetic variation and epigenetics. The genetic determinants of common and complex phenotypes are difficult to resolve even though their heritability is recognised. Recent genome-wide association studies (GWAS) for common diseases has identified many new disease susceptibility associated loci. These loci often lie in non-coding regions of the genome and disease associated genetic variants are proposed to act by modulating gene expression. This thesis investigated genetic variation as determinants of gene expression in the context of the immune system especially focused on the innate immune and inflammatory responses. Different primary human immune cell types were collected from healthy volunteers of European ancestry to achieve this. In order to identify genetic variants associating with gene expression, expression quantitative trait loci (eQTL) mapping was conducted in a cell type specific manner. The primary dataset (n=288) consists of CD19+ B-cells from the adaptive immune system and CD14+ monocytes from the innate immune system. 78% of the total cis eQTL were found to be cell type specific and include genes relating to their roles in the immune response. Trans eQTL showed greater cell type specificity and include master regulatory eQTL on the LYZ locus at chromosome 12q15 in monocytes and the KLF4 (9p31) in B-cells. The identified eQTL are implicated in association with autoimmune disease susceptibility including inflammatory bowel disease, diabetes and rheumatoid arthritis. The second analysed dataset (n=64) consists of CD14+ monocytes and macrophages differentiated ex vivo. Macrophages are involved in many inflammatory diseases as well as in the innate immune response. The differential gene expression and eQTL mapping analyses were conducted to investigate macrophages specific gene expression signatures and associations to genetic variants. Macrophage eQTL are involved in signal transduction for the inflammatory response (IL1RN and STAT4) and lipid metabolism (PPARG) with implication for metabolic disease association. The eQTL analyses using primary immune cell types provide insights into genetic variation in association to gene expression which is involved in autoimmunity and disease susceptibility.